PELAKSANAAN PEMBAYARAN PAJAK HIBURAN MALAM DI KOTA SAMARINDA DITINJAU BERDASARKAN PERATURAN DAERAH KOTA SAMARINDA NO. 4 TAHUN 2011 TENTANG PAJAK DAERAH - Genesis Alva Vania Manembu (Universitas 17 Agustus 1945 Samarinda, 2020)
AbstractIn this study, the author discusses the title “Implementation of night entertainment tax payments in Samarinda City reviewed based on the Regional Regulation of Samarinda City No.4 of 2011 concerning Regional Taxes”. Regional Tax is one of the components of revenue used to finance regional needs. Entertainment tax is one of the regional taxes collected by the government and managed by the regional by the regionalgovemment as a source of regional revenue. The formulation of the problem in this research is how the implementation of the payment of night entertainment of tax and law enforcement payments seen from regional Regional Regulation No.4 of 2011 which aims to determine the payment of tax on night entertainment. This study uses an empirical juridical method, namely field research. It has been concluted through data sourcesthat the authors get from the office of the Regional Revenue Agency that the implementation of the payment of night entertainment tax has been going well and in accordance with the procedure. Nightclub business entities in Samarinda city also have a positive awareness and influence to achieve the target of Regional Revenues.